Determination of the lot size using the Wagner-Whitin algorithm under the Constraint Theory / Case Study of Diyala Public Company - جواد مها كامل; حسن عمر فلاح (Journal of Economics and Administrative Sciences, 2019)
International companies are striving to reduce their costs and increase their profits, and these trends have produced many methods and techniques to achieve these goals. these methods is heuristic and the other Optimization.. The research includes an attempt to adapt some of these techniques in the Iraqi companies, and these techniques are to determine the optimal lot size using the algorithms Wagner-Whitin under the theory of constraints. The research adopted the case study methodology to objectively identify the problem of research, namely determining lot size optimal for each of the products of electronic measurement laboratory in Diyala and in light of the bottlenecks in workstations or constraints that limit capacity. Which is suffering from the Electronic Standards Lab with its four products. The research aims to identify the bottlenecks in the work stations through the use of some of the tools of the theory of constraints and work to address them by determining the optimal mix, as well as work to determine the optimal lot size for each product and to ensure that these the least cost. As the importance of research is to draw the attention of the company to the use of scientific methods to deal with the problems in this research to be a starting point towards a comprehensive understanding of those methods and the benefits of their use. The results also showed the advantage of the Wagner-Whitin algorithm in determining the optimal size of the lot on the company method and the adoption of cost standards. Taking into account the recommendations of the research, which is the adoption of scientific methods in determining the size of the lot and the application of the theory constraints and layout of the laboratory and training employees to use these techniques to achieve the company the ability to reduce the cost and thus increase profits